The role of a genetic counsellor in a support group for Huntington disease - du Toit, Maxine (Department of Clinical Laboratory Sciences, 2020)
Genetic counselling students are encouraged to become involved with support groups for genetic conditions. However, their roles within these groups are not well defined and poorly understood and ethical concerns have been raised regarding the appropriateness of such involvement. A limited number of international studies have examined the role of a genetic counsellor in a support group. These studies report broadly on the matter but lack the personal response that qualitative data produces. South African literature is even more limited and no studies (both locally and internationally) have attempted to describe the role of a genetic counsellor in a support group for Huntington disease. This study examines the role of a genetic counsellor in a Huntington Disease support group, specifically the Huntington’s Association of South Africa (HASA). A qualitative research approach was used to interview 17 people who have been involved with HASA in the past seven years. In-person and telephonic interviews were conducted with five genetic counsellors and one psychologist. Two separate focus groups were conducted with a total of 11 support group members and one genetic counsellor (who was also interviewed in-person). The interviews and focus groups were audio recorded and transcribed by a combination of an online software program named Sonix Transcription and manual transcription by the researcher herself. Thematic analysis was done and the results were grouped according to the following five themes that emerged from the data: 1) Is there a role?, 2) Information provider, 3) Emotional support, 4) Practical helper, and 5) Community member. It was found that there is a role for a genetic counsellor in a HASA support group and that the relationship that is formed though such involvement can be mutually beneficial to both the support group members and the genetic counsellor. The genetic counsellor’s role was found to be wide and included specialist and practical roles, as indicated by above mentioned themes two to five. These findings cannot be extrapolated to apply to all support groups due to the unique characteristics and function of different support groups. This was evident in this case as the two branches in SA (Western Cape and Gauteng) seem to function very differently. The research can, however, be used as guideline for involvement with other support groups. This 9 study’s findings made a unique contribution in that it documented in detail the genetic counsellor’s involvement in support groups. The study found that all the participants agreed that HASA should have access to a genetic counsellor, thus it is recommended that future studies should explore the role of a genetic counsellor in support groups for other genetic conditions, as those groups could also find it beneficial.